Proceedings. IEEE INFOCOM '98, the Conference on Computer Communications. Seventeenth Annual Joint Conference of the IEEE Compu
DOI: 10.1109/infcom.1998.662933
|View full text |Cite
|
Sign up to set email alerts
|

A scalable control topology for multicast communications

Abstract: Large-Scale multicast applications for the Internet require the availability of multicast protocols that enhance the basic connectionless IP Multicast service. A critical requirement of such protocols is their ability to support a large group of simultaneous users. In this paper, we present a new approach for distributing control information within a multicast group. The goal of our approach is to scale to very large group sizes in excess of 100,000 users. Multicast group members are organized a s a l o gical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…This topology completely ignores the network topology [19]. Data is disseminated using trees which are embedded in the hypercube [21].…”
Section: Comparative Evaluation Of Overlay Topologiesmentioning
confidence: 99%
“…This topology completely ignores the network topology [19]. Data is disseminated using trees which are embedded in the hypercube [21].…”
Section: Comparative Evaluation Of Overlay Topologiesmentioning
confidence: 99%
“…A number of research and commercial large-scale parallel machines have been built based on the hypercube network topology [14,22,28,29,31]. Very recently, research has also shown that fault tolerant hypercube networks of large size (e.g., over many thousand nodes) can be used as an effective control topology in supporting large-scale multicast applications in the Internet [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Producing a reliable multicast protocol that scales well with the number of receivers, in terms of network traffic and the processing required of the source and receivers, has proven to be a challenge, as demonstrated by the number of approaches taken in the past (e.g., [5,7,9,11,12,14,15,19,21,20,[27][28][29]). Moreover, as protocols for multicast error control are developed, mechanisms must also be developed for multicast congestion control [3,6,17], similar to those developed for such unicast reliable protocols as TCP [8].…”
Section: Introductionmentioning
confidence: 99%